Prepregnancy Body Mass Index and Risk of Preeclampsia: A Meta-Analysis - Suwarsa, Nurul Azizah; Fadli Ananda; H. Muh Nur Abadi (HM Publisher, 2024)
Preeclampsia is a serious complication of pregnancy and is associated with an increased risk of maternal and fetal morbidity and mortality. Body mass index (BMI) before pregnancy has been identified as a potential risk factor for preeclampsia. This study aims to conduct a meta-analysis to evaluate the relationship between BMI before pregnancy and the incidence of preeclampsia, as well as identify effective prevention strategies. A literature search was conducted on the PubMed, Scopus, and Web of Science databases to identify observational studies published between 2018 and 2024. Studies that met the inclusion criteria had their data extracted and analyzed using a random effects model. Heterogeneity between studies was evaluated using the I2 statistic. Subgroup analyzes were performed based on geographic region and study design. A total of 25 studies with 534,000 respondents were included in this meta-analysis. The results of the analysis showed that increasing BMI before pregnancy was significantly associated with an increased risk of preeclampsia 2.22 (95% CI: 1.72-3.35). Subgroup analyzes revealed that these associations were consistent across geographic regions and study designs. This meta-analysis provides strong evidence that BMI before pregnancy is an independent risk factor for preeclampsia. Interventions to optimize BMI before pregnancy, such as nutritional counseling and promotion of physical activity, may be an effective preventive strategy to reduce the risk of preeclampsia.